The answer to that would be many
Answer:
a = 2
b = 3
c = 8
Step-by-step explanation:
<em>2^5/4</em>=<em>2^5/2a</em>=<em>2^b</em>=<em>c</em>
<em>2^5/4</em>, 2^5 = 32, 32/4 = 8
so c, being what all of this is equal to, is 8
<em>2^5/2a</em>, 2*2=4
so a = 2
<em>2^b </em>= 8, ∛8 = 3
so b = 3
Hope my explanation makes sense :)
Answer:
f^-1 (x) = (1 - x)/3.
Step-by-step explanation:
f(x) = -3x + 1
3x = 1 - f(x)
x = (1 - f(x)) / 3
So f^-1 x = (1 - x)/3.
Answer:
11250 cm^3
Step-by-step explanation:
45cm × 25cm × 10cm =11250cm